1989
DOI: 10.1111/j.1471-4159.1989.tb09262.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Inositol Phosphates Induced by Chlorpromazine in C6 Glioma Cells

Abstract: Chlorpromazine, a cationic amphiphilic drug known to affect phospholipid metabolism, greatly increases the generation of inositol phosphates in C6 glioma cells. When a pulse-chase protocol with myo-[2-3H]inositol as the radioactive precursor was used, the peak increase in radioactivity of inositol phosphates was observed at 20 min. The drug decreased inositol tetrakisphosphate labeling as a percentage of inositol trisphosphate in a dose-dependent manner. It also increased the labeling of the inositol-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1990
1990
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…2). In contrast to a previous observation on another NB cell line [23] we did not find any PKC /I mRNA. This could be ascribed to differences in method evaluation or to a further cell clone-specificity.…”
Section: P-pcontrasting
confidence: 99%
See 2 more Smart Citations
“…2). In contrast to a previous observation on another NB cell line [23] we did not find any PKC /I mRNA. This could be ascribed to differences in method evaluation or to a further cell clone-specificity.…”
Section: P-pcontrasting
confidence: 99%
“…Previous reports have documented changes in PKC during neuronal maturation [22][23][24]331. While these studies have demonstrated modulation of some PKC isoenzymes during treatment of neural cells with PKC inhibitors or they have focused on only few PKC isoforms, they have, however, failed to address whether true differentiation-promoting agents, such as IFN-)I and RA, affect the individual isoforms in a differential manner within the same neuronal model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation